Analisis Kemampuan Membaca Lancar Level 3 - Gentis Ayu Wariyanti; Chandra Chandra; Inggria Kharisma (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This study aims to analyze the fluent reading ability of level 3 elementary school students in grade 3 through the aspects of pauses, intonation, expression, and understanding of the text content. The approach used is qualitative with a question and answer method. Five students read the text "Malin Kundang", then assessed based on four main aspects of fluent reading. The results of the study showed that students' reading abilities in the aspects of pauses (average 4.0), intonation (3.6), and expression (3.4) were in the good category. However, the aspect of understanding was still classified as sufficient (average 2.4), which indicates the need for more effective learning strategies to improve understanding of the text content. These findings confirm that although students are able to read with appropriate pauses, intonation, and expression, their understanding of the meaning of the story is still not optimal. This study recommends more focused and enjoyable reading learning so that students not only read fluently technically, but also understand the content of the reading in depth.